Ambiental justice and Danilo Dolci (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
The present article is retrieved from my doctoral dissertation entitled “A Theory of Justice for Environmental Justice. A Comparative Analysis between Italy and Germany”. The main goal of this paper is to shed a light on the EJ discourse in Italy, its evolutionary scheme, and historical roots. To this end, a systematic survey of the literature, as well as a portrait of the major strengths and key features of the EJ in Italy are provided. By looking at the rise of the EJ movements in Italy, a particular attention is devoted to Danilo Dolci's social commitment during the postwar period. Indeed, an expanded reading of Dolci not only as an anti-mafia and non-violent activist but also as the father of EJ in Italy is provided.Keywords: Collective empowerment, Danilo Dolci, Environmental Justice, environmental conflicts, environmental policies.